Optimizing Fuel Tank Truck Distribution to The Gas Station by Anylogistix (Case Study: Fuel Terminal Sorong) - Rumalutur, Yizri Ievana Febrianty; Sukarno, Iwan (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
PT Pertamina Patra Niaga Sorong Fuel Terminal is a company engaged in receiving, stockpiling, and distributing. Fuel stockpiled in the tank will be distributed through a tank truck with a capacity of 5,000 liters. The limited capacity of the tank truck makes the distribution less than optimal. The limited tank truck capacity triggers problems in the distribution system, especially considering that the life of 3 of the 6 existing tank trucks will expire in 2024. By considering the remaining time, the company needs to evaluate the distribution facilities that will be used and one of the solutions is to vary the capacity of the tank trucks. This problem can be solved through several considerations such as the urgency of tank truck needs, the amount of fuel needed, the infrastructure of the Sorong region, and some data that will be processed using Anylogistix. The results show that with the new tank truck capacity variations, namely 28,000 liter and 15,000 liter, in the selected periods it is more efficient by 24.58%, 3.44%, 31.6%, 26.37%, 30.67%, and 23.65% in terms of time compared to without variation. In addition, 445.6 liters of fuel can be saved in a month. All demands can be met from the minimization results so that this solution can optimize the distribution carried out and have a positive impact on the company.